TRADISI PARNO ADAT MASYARAKAT KUMUN KECAMATAN KUMUN DEBAI KOTA SUNGAI PENUH PROVINSI JAMBI DAN EKSISTENSINYA DI ERA GLOBALISASI - Anisa Firda Rahma; Prof. Dr. Isjoni, M.Si '; Drs. Kamaruddin, M. Si ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstrack: This thesis discusses the tradition Parno Kumun Indigenous community, Jambi Province and Its existence in the era of globalization. Parno Adat is one of Kumun's oral tradition are classified into Lyrical Prose. Parno have a pattern that is similar to rhymes and phrases. People who present it is tengganai (boys elder in the family) and Stakeholder Customary (Depati Nenek Mamak), Parno Adat only delivered in a ceremony custom shades. The purpose of this study was to determine and explain the traditions of Parno Adat and driving factors of its existence in the era of globalization. This research was conducted using the method of history or historical. Data were collected through observation, library research, interviews, and comparative studies. The results showed that Parno Adat has an important position in traditional ceremonies in Kumun society, every ceremonies are always opened and closed through the delivery Parno, even the core of the event was also filled by delivery Parno. So, Parno Adat is the lifeblood of all traditional ceremonies so that people never leave tradition of Parno Adat and keep it amid the onslaught of globalization today.Key words: oral traditions, parno adat.